Methanol modified type hydrogen production catalyst and production method of the same

The core-shell structured catalyst with optimized metal distribution in the core and shell addresses the inefficiencies of conventional silica-based catalysts, achieving improved methanol conversion rates and catalyst utilization.

JP2024175892AInactive Publication Date: 2024-12-19UNIVERSITY OF KITAKYUSHU +1

Patent Information

Application Number
JP2023093976
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional methanol reforming catalysts using silica as a carrier face challenges in maximizing catalyst utilization rate due to difficulty in accessing the interior pores, leading to inefficient hydrogen production.

Method used

A core-shell structured catalyst is developed where catalyst metal is dispersed both in the core and shell, with a higher concentration in the shell, utilizing a sol-gel method to enhance catalyst dispersion and support, and an activation process to improve efficiency.

Benefits of technology

The core-shell structure significantly enhances catalyst utilization rate and methanol conversion efficiency compared to conventional catalysts, achieving higher methanol conversion rates with optimized metal distribution and reduced sintering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024175892000001_ABST
    Figure 2024175892000001_ABST
Patent Text Reader

Abstract

To provide a methanol modified type hydrogen production catalyst capable of carrying methanol to inside of a catalyst and improving a use ratio of the catalyst metal, for solving problems in prior arts for having silica as a carrier and carrying copper particles as catalyst component.SOLUTION: There is provided a core shell structure catalyst in which, relative to mass% of a catalyst metal amount of catalyst metal dispersed in a porous core, mass% of catalyst metal (equal to the catalyst metal dispersed in the core) dispersed in the shell formed on the core surface, is increased, therefore relative to a catalyst using the same amount of catalyst metal, a catalyst having high methanol transformation efficiency (namely, catalyst having high use ratio of the catalyst metal) can be provided.SELECTED DRAWING: Figure 9
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for producing hydrogen by methanol reforming. [Background technology]

[0002] Currently, fossil fuels such as oil and natural gas are used as fuel for internal combustion engines in automobiles and other vehicles. Carbon dioxide, which is produced when internal combustion engines burn fossil fuels, has been pointed out as a cause of global warming and environmental problems. Instead of internal combustion engines that use gasoline and other fuels to power automobiles, electric vehicles that run their motors on electricity stored in storage batteries, hydrogen vehicles that run on internal combustion engines that use hydrogen as fuel, and fuel cell vehicles that run their motors on electricity generated by an electrochemical reaction between hydrogen and oxygen have all been developed and put into practical use. Electric vehicles that use electricity obtained from renewable energy sources have the lowest CO 2 Although emissions are thought to be low, they require large amounts of diverse mineral resources, such as lithium and cobalt, which are used in the lithium-ion batteries that store electricity, and their production and refining pose environmental problems such as water and soil pollution. On the other hand, fuel cell vehicles do not have as large an environmental impact during production as electric vehicles, and by carrying fuel with a higher energy density than lithium-ion batteries, they are expected to be a technology that can ensure the driving range of large vehicles in particular. When so-called green hydrogen, which is produced by water electrolysis using electricity obtained from renewable energy sources, or reformed plant-derived biofuel is used as fuel, CO 2 Emissions are expected to be lower than those from battery vehicles charged from the grid.

[0003] Hydrogen is produced by the decomposition reaction of hydrocarbons using methods such as partial oxidation reaction, steam reforming, and autothermal. Currently, the mainstream method of producing hydrogen is steam reforming of natural gas (main component is methane), which is a high-temperature reaction of about 700°C. Among various hydrocarbons, methanol steam reforming (hereinafter referred to as methanol reforming method or methanol reforming in this specification) is superior in that the reaction proceeds at a low temperature of about 300°C using liquid fuel with excellent portability. In addition to using natural gas as the raw material, methanol can also be obtained from biomass, which significantly reduces the environmental load.

[0004] Catalysts play an extremely important role in the production of hydrogen through methanol reforming. The main requirements for catalysts are to improve catalytic activity, which contributes to reforming efficiency, to stabilize catalytic activity, to improve the rate (utilization rate) of catalytic metals used in reforming, and to suppress the generation of harmful by-products.

[0005] The metals used in methanol reforming are common materials such as copper, nickel, and iron, except for the precious metal ruthenium. However, the prices of these metals have already risen sharply due to increased demand, making it necessary to reduce their usage (increase catalytic activity and / or improve utilization rate).

[0006] The invention disclosed in Patent Document 1 is a methanol-reforming type hydrogen production catalyst for hydrogen generation, previously invented by the inventor of the present invention, in which copper particles are dispersed on silica as a support, and the weight ratio of silica to copper is between 1:1 and 1:1.63. The catalyst is disclosed as a porous catalyst that can obtain excellent catalytic activity by obtaining a sol containing copper in the above range by a sol-gel method from a sol prepared by adding copper particles to a mixture of silicon alkoxide and water and stirring the mixture. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6936338 Summary of the Invention [Problem to be solved by the invention]

[0008] As mentioned above, the catalyst described in Patent Document 1 is a better catalyst than the conventional products at that time, but it uses silica produced by the sol-gel method as a support, and although it is porous, when it is granulated to a practical particle size of several mm by binder molding or powder molding, the reaction gas does not easily reach the inside through the pores of the silica, and the utilization rate of the catalyst metal is difficult to increase. Therefore, the objective of the present invention is to further improve the utilization rate of the catalyst. [Means for solving the problem]

[0009] In order to solve the above problems, the first invention is A catalyst-dispersed porous core in which a catalyst metal is dispersed to a central portion; a catalyst-dispersed shell in which the catalyst metal is dispersed on the surface of the catalyst-dispersed porous core; The present invention provides a methanol-reforming hydrogen production catalyst having a structure that allows methanol vapor and water vapor in a reaction vessel to permeate through the catalyst-dispersed porous core and to come into contact with the dispersed catalytic metal in the catalyst-dispersed porous core and the dispersed catalytic metal in the catalyst-dispersed shell.

[0010] Furthermore, as a second invention, based on the first invention, The catalyst metal is at least one metal selected from copper, nickel, iron and ruthenium, or an alloy or intermetallic compound containing at least one metal selected from copper, nickel, iron and ruthenium, and the catalyst metal of the catalyst-dispersed porous core and the catalyst-dispersed shell are the same metal.

[0011] Furthermore, as a third invention, based on either the first or second invention, The catalyst-dispersed porous core is made of at least one of silicon oxide, aluminum oxide, zeolite, carbon, and metal oxide.

[0012] Furthermore, as a fourth invention, based on any one of the first to third inventions, A methanol reforming hydrogen production catalyst is provided, in which the proportion of catalytic metal in the catalyst-dispersed porous core is 5 to 25 wt %, and the proportion of catalytic metal in the catalyst-dispersed shell is 45 to 55 wt %.

[0013] Further, as a fifth invention, based on any one of the first to fourth inventions, A methanol-reforming hydrogen production catalyst is provided, the average particle size of which is from 1 to 5 millimeters.

[0014] Furthermore, as a sixth invention, A core preparation step of preparing a porous granular core; A pretreatment step of cleaning the prepared porous core to remove impurities; a core immersion step of immersing the pretreated porous core in a solution having a catalytic metal dissolved therein; a core immersion step of immersing the pretreated porous core in a solution containing a water-soluble catalytic metal salt; a core catalyst metal supporting step of thermally decomposing the catalyst metal salt dispersed in the porous core to support the catalyst metal on the porous core; a precursor film forming step of immersing the porous core that has been subjected to the core catalyst metal supporting step in a hydrolysis sol solution of silicon alcoholate in which a water-soluble catalyst metal salt is dissolved, to form a precursor film on the surface of the porous core; a shell forming step of thermally decomposing a water-soluble catalytic metal salt in the precursor film formed in the precursor film forming step to form a catalyst-dispersed shell; The present invention provides a method for producing a methanol-reforming hydrogen production catalyst comprising the steps of:

[0015] Furthermore, as a seventh invention, The sixth aspect of the present invention provides a method for producing a methanol-reforming hydrogen production catalyst, comprising an activation step of performing an activation treatment in a reducing atmosphere in the temperature range of 280°C to 320°C before use.

[0016] Further, as an eighth invention, based on either the sixth or seventh invention, The catalyst metal is one or more metals selected from copper, nickel, iron and ruthenium, or an alloy or intermetallic compound containing one or more metals selected from copper, nickel, iron and ruthenium, and the catalyst metals of the core and shell are the same metal. Effect of the Invention

[0017] The present invention having the above-mentioned configuration can provide a methanol-reforming hydrogen production catalyst that has a further improved catalyst utilization rate compared to conventional methanol-reforming hydrogen production catalysts that use silica as a support and copper particles as a catalytic component. [Brief description of the drawings]

[0018] [Figure 1] Schematic cross-sectional view of the methanol reforming type hydrogen production catalyst of the present invention. [Diagram 2] Relationship between the amount of catalytic metal (Cu) dispersed in the core (wt%) (dispersed in the core only, not dispersed in the shell) and the methanol conversion rate (%) [Diagram 3] Pore ​​distribution of a sample prepared by the sol-gel method using only shell material [Figure 4] Relationship between the amount (wt%) of catalytic metal (Cu) dispersed in the shell (not dispersed in the core) and the methanol conversion rate (%) [Diagram 5] Relationship between shell coating times and methanol conversion rate (%) [Figure 6] Relationship between the amount (wt%) of catalytic metal (Cu) dispersed in the core and the methanol conversion rate (%) when the shell is coated once [Figure 7] Relationship diagram of methanol conversion rate (%) for each specification using the weight (g) of catalytic metal (Cu) per 1 g of catalyst as a scale [Figure 8] FIG. 1 is an explanatory diagram of a method for producing a core-shell structured methanol-reforming hydrogen production catalyst according to the present invention. [Figure 9]Flowchart 1 for producing the core-shell structured methanol reforming hydrogen production catalyst of the present invention [Figure 10] Flowchart 2 for producing the core-shell structured methanol reforming hydrogen production catalyst of the present invention [Figure 11] SEM image of the surface of silica gel manufactured by Fuji Silysia Chemical Ltd. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] <Steam reforming reaction of methanol> First, let us explain the reaction between a catalyst carrying a catalytic metal and methanol. Vaporized methanol and water vapor are mixed and introduced into a reactor or other vessel containing a catalyst for methanol reforming. When the temperature inside the reactor is kept between 250°C and 350°C, the hydroxyl groups and other hydrogen atoms in the methanol are removed by the catalytic metal, forming H. 2 For example, the reaction formula is CH 3 OH+H 2 O → 3H 2 +CO 2 During methanol reforming, CH is an unintended by-product. 3 OH → CO+2H 2 , or H 2 +CO 2 →CO+H 2 Carbon monoxide is also produced, as is O. The by-product CO 2 It is also important to reduce or eliminate the production of carbon monoxide and other substances that are harmful to the human body.

[0020] <Steam reforming of methanol: By-product: Suppression and removal of carbon monoxide> To suppress the production of carbon monoxide, which is toxic to humans, during methanol reforming, there are several methods, such as using Cu as the catalytic metal, reducing and activating the catalytic metal before methanol reforming to increase its surface area, lowering the reaction temperature (raising the temperature increases the amount of carbon monoxide produced), and adjusting the ratio of water vapor and methanol vapor. Carbon monoxide that is produced can be oxidized to carbon dioxide using an oxidation catalyst, reacted with carbon monoxide and water vapor to produce carbon dioxide and hydrogen (water-gas shift reaction (WGS)), or pressure transformation adsorption (PSA) can be used.

[0021] <Steam reforming of methanol: By-product: Suppression and removal of carbon dioxide> The carbon dioxide produced by the methanol reforming reaction can be selectively collected and removed together with hydrogen using liquid absorption or membrane separation methods. In the liquid absorption method, an appropriate liquid is selected from methyldiethanolamine (MDEA), triethanolamine (TEA), polyethylene glycol (PEG), dimethylethanolamine (DMEA), polyamine (PA), diethylene glycol (DEG), etc., as the absorption liquid.

[0022] For example, when a methanol reforming type hydrogen production device is attached to a fuel cell and operated, a membrane that allows hydrogen to pass but does not allow carbon monoxide and carbon dioxide to pass through can be installed on the outlet side of the methanol reforming reaction tank (membrane separation method) so that only hydrogen can be supplied to the fuel cell. Membranes used for separation include, for example, Nafion (registered trademark) membranes, which are copolymers of fluororesins based on sulfonated tetrafluoroethylene; polymer membranes such as polyvinyl chloride (PVC) and polyethylene (PE); ceramic membranes made of ceramic materials such as aluminum oxide and zirconium; and hydrogen-permeable metal membranes made of Pd or V.

[0023] Hereinafter, embodiments of the present invention will be described with reference to the drawings. Note that the present invention is not limited to these embodiments, and can be embodied in various forms without departing from the spirit of the present invention.

[0024] In this specification, the methanol conversion rate (%) indicates the ratio of the amount of methanol reformed into hydrogen, carbon dioxide, etc. to the amount of methanol before reforming. The catalysts for each specification were evaluated by measuring the methanol conversion rate (%) of each catalyst.

[0025] <Overview of embodiment 1> The methanol-reforming hydrogen production catalyst of this embodiment is configured to have a core-shell structure in which a granular catalyst-dispersed porous core, in which a specific catalyst metal is dispersed inside the porous core, is coated with a catalyst-dispersed shell containing a water-soluble catalyst metal salt prepared by a sol-gel method. In particular, the catalyst metal dispersed in the core and the shell is the same metal, and the amount of the catalyst metal dispersed in the shell (wt % relative to the shell) is greater than the amount of the catalyst metal dispersed in the core (wt % relative to the core).

[0026] In the examples of this specification, both the core and the shell are made of Cu as a catalyst metal and SiO as a support. 2 In the present specification, the catalyst-dispersed porous core may be abbreviated as "core" and the catalyst-dispersed shell may be abbreviated as "shell". Below, the structure of the methanol reforming hydrogen production catalyst will be described first, and then the manufacturing method will be described. When describing the structure, the range of the weight percentage (sometimes expressed as wt%) of the catalyst metal will also be described.

[0027] <Configuration of embodiment 1>: Mainly corresponds to claim 1 The methanol-reforming hydrogen production catalyst of embodiment 1 has a core-shell structure in which a catalyst-dispersed porous core has a catalytic metal dispersed up to the center of the support of the porous core, and at least a portion, preferably all, of the surface of the catalyst-dispersed porous core is covered with a catalyst-dispersed shell having the same catalytic metal as that of the catalyst-dispersed porous core (see FIG. 1 ).

[0028] <Embodiment 1: Purpose of Core-Shell Structure> As described later, the catalyst of the present invention is configured so that the weight percentage of the catalytic metal is higher in the shell covering the core than in the core. This is because it is considered that the rate at which methanol reacts with the catalyst metal near the center of the core is higher than the rate at which methanol travels through the pores of the catalyst core and reacts with the catalyst metal near the center of the core. However, if too much catalytic metal is concentrated only in the shell, sintering occurs, in which the catalytic metal in the shell gathers and aggregates at the temperature during the reforming reaction. Sintering can occur not only in the shell but also in the catalytic metal dispersed in the core, but at high temperatures such as the reaction temperature during methanol reforming (e.g., 300°C), even if the temperature is below the melting point of the catalytic metal, the metal atoms on the particle surface of the catalytic metal dispersed on the surface of the support material in the shell or core move actively, causing surface diffusion, in which the catalytic metal moves to the support surface. The surface-diffused atoms move one after another, come into contact with adjacent catalytic metal particles at a distance of nm and become integrated. The larger the catalytic metal particle, the smaller the surface energy of the particle surface and the more stable it is, so when surface diffusion occurs, the atoms of the small catalytic metal particles break away and become smaller, while the atoms of the large particles gather and grow larger. Sintering also includes semi-sintering, in which the surface of the metal particles melts when heated to a temperature below the melting point, making corners and protrusions round and smooth (reducing the surface energy). The surface area of ​​the catalytic metal that has aggregated after sintering is smaller than the total surface area of ​​the dispersed catalytic metal before aggregation, so the utilization rate of the catalyst decreases and the methanol conversion rate decreases. For this reason, a smaller weight percent of the catalytic metal is dispersed and supported in the porous core than in the shell to contribute to methanol reforming.

[0029] <Embodiment 1 Configuration: Catalyst-dispersed porous core (0101)> The catalyst-dispersed porous core is configured so that the catalyst metal is dispersed to the center. When an aqueous solution of copper nitrate or the like containing Cu is permeated into the porous core for dispersion, the core can be permeated by capillary action by simply immersing the core in the aqueous solution, but more effective permeation can be achieved by vacuum permeation (adding an aqueous solution of copper nitrate or the like in a vacuum, and then gradually returning the pressure to atmospheric pressure), promoting permeation by vibration (ultrasonic vibration, etc.), or temperature adjustment (increasing the temperature to decrease the viscosity of the liquid to be permeated). The porous core in which the catalyst metal is dispersed to the center is a granular object having a shape such as a sphere, cube, rectangular parallelepiped, short column, or finely crushed fragments.

[0030] <Embodiment 1 Configuration: Catalyst-dispersed porous core (0101): Catalyst metal>: Mainly corresponds to claim 2 The catalytic metal dispersed in the pores of the core is one or more metals selected from copper, nickel, iron and ruthenium, or an alloy or intermetallic compound containing one or more metals selected from copper, nickel, iron and ruthenium, and is configured so that the catalytic metal of the catalyst-dispersed porous core and the catalyst-dispersed shell described below are the same metal.

[0031] As the catalytic metal, transition metals that have highly reactive d-electrons and can take various oxidation numbers are suitable. Among transition metals, Cu, Fe, Ni, Ru, etc. are suitable as catalytic metals for methanol reforming because they have a high methanol conversion rate, produce little CO, which is not a desired reaction product, are highly resistant to the temperature and environment during the reaction, and are relatively inexpensive and easily available. Therefore, any one or more metals selected from Cu, Fe, Ni, and Ru, or an alloy or intermetallic compound containing one or more metals selected from Cu, Fe, Ni, and Ru are preferred. Other transition metals include Co, Pt, Rh, Pd, Ir, Mo, W, La, Ce, etc., and transition metal alloys such as CuNi and CuCo can be used. In addition, Cu-Zn-Al, Cu-Zn-Cr, Cu-Ni-Zn, Rh-Mn, Pd-Zn, Cu-ZrO, etc. can be used as intermetallic compounds. 2 system, Ni-Cl system, ZrO 2 can be used as a catalyst.

[0032] <Embodiment 1 Configuration: Catalyst-dispersed porous core (0101): Core material>: Mainly corresponds to claim 3 In the examples of the present specification, the catalyst-dispersed porous core is exemplified as being made of silicon oxide, but may be made of one or more of silicon oxide, aluminum oxide, zeolite, carbon, and metal oxide.

[0033] The core material must have the following four characteristics to support the catalytic metal used in gas reactions: (1) High loading capacity: The support material must have a porous structure with many fine holes to uniformly disperse the catalytic metal particles and ensure a large surface area for the catalytic metal, thereby increasing the contact area with the reactants and improving the reaction rate. This requires a high loading capacity to effectively support the catalytic metal. (2) Thermal stability: Since gas reactions usually take place at high temperatures, chemical stability with little thermal expansion or contraction is required. (3) Chemical stability: It is desirable for the support material to be chemically inactive and chemically stable under reaction conditions to avoid unwanted interactions with reactants and products. (4) Interaction with supported catalytic metal: It is desirable that the affinity with the catalytic metal is high and that the particles of the supported catalytic metal are supported in a stable state. It is also important that electron transfer occurs between the catalytic metal and the catalyst so that the catalytic reaction proceeds efficiently. The interaction between the catalytic metal and the support must be good. As a support material satisfying these characteristics, a support made of one or more of the above-mentioned silicon oxide, aluminum oxide, zeolite, carbon, and metal oxide is used.

[0034] <Embodiment 1 Configuration: Catalyst-dispersed porous core (0101): Weight percent range of catalyst metal>: Mainly corresponds to claim 4 The ratio of the catalytic metal dispersed in the pores of the core is configured to be 5 to 25 wt%. This ratio range is determined from the results of investigating the methanol conversion rate (%) (the ratio of the amount of methanol before contacting the catalyst to the amount of methanol reacted by reforming) for each sample (1 g) prepared by dividing the weight percent of Cu dispersed in the core alone (without shell) of the hydrogen production catalyst of the present invention (FIG. 2). In the range where the ratio of the catalytic metal dispersed in the pores of the core is 0 wt% or more and less than 5 wt%, there are few catalytic active sites, so the lower limit is set to 5 wt% or more. The inventor of the present invention found during experiments that when the ratio of the catalytic metal dispersed in the pores of the core exceeds 25 wt%, sintering of the catalytic metal occurs due to the temperature during the methanol reforming reaction. If sintering occurs, the methanol conversion rate decreases, so the upper limit of the ratio of the catalytic metal dispersed in the pores of the core is set to 25 wt%. The lower limit was determined from a quadratic approximation line for the methanol conversion measurement results when the Cu weight percentage of the core was divided into 10, 20, and 30 wt%, as shown in Figure 2. The lower limit of the range of the weight percentage of Cu dispersed in the core is preferably 5 wt% or more (methanol conversion rate of 50% or more) because there are few catalytic active sites at less than 5 wt% as described above, more preferably 7.5 wt% at which the methanol conversion rate is 60% or more, and most preferably 10 wt% or more at which the methanol conversion rate is 65% or more. The upper limit is 25 wt% or less as described above due to the sintering.

[0035] To check for sintering of catalytic metals, a TEM (transmission electron microscope) can be used to evaluate minute areas, or X-ray diffraction can be used to check for changes in the crystal structure. Carbon monoxide or hydrogen chemical adsorption can also be used. Carbon monoxide and hydrogen selectively adsorb to many metals. This property can be used to evaluate the metal surface area. Alternatively, the catalyst surface can be observed with a SEM (scanning electron microscope).

[0036] <Embodiment 1: Composition: Catalyst-dispersed shell (0102)> The catalyst-dispersed shell is configured to disperse the catalyst metal on the surface of the catalyst-dispersed porous core. The catalyst-dispersed shell is, for example, silica having a three-dimensional network structure formed by a sol-gel method. The catalyst-dispersed shell prepared by the sol-gel method is preferably porous in order to react the catalyst metal dispersed inside the shell itself with methanol, or to react the catalyst metal dispersed on the surface of the core of the lower layer and inside the core with methanol. The shell may be porous having pores reflecting the porosity of the core, but it is most preferable that the shell itself is porous without necessarily reflecting (or may reflect) the porosity of the core.

[0037] To evaluate the porosity of the shell material, the completed shell was composed of 55 wt% Cu and SiO 2 A shell-forming material having a composition of 45 wt% was fabricated by the sol-gel method using the shell material alone without using a core. The pore distribution of the prototype was examined, and the results are shown in FIG. 3. The pore distribution was examined by SF-Plot analysis (Microtrack-Bell, Inc., measurement by nitrogen adsorption), which is a gas adsorption method. The pore diameter of the first peak was 0.66 nm, and the pore diameter of the second peak was 0.97 nm, confirming that the shell of the embodiment of this specification is a porous shell having pores.

[0038] <Embodiment 1 Configuration: Catalyst-dispersed shell (0102): Shell material> The materials that make up the shell, other than the catalytic metal, are silica obtained from silicon alcoholates such as tetramethoxysilane and tetraethoxysilane, but cerium oxide (CeO 2 ), aluminum oxide (Al 2 O 3 ), titanium dioxide (TiO 2 Inorganic crystal components such as aluminum nitride (AlN), silicon carbide (SiC), and beryllium oxide (BeO) that improve the mechanical properties, heat transfer properties, and heat resistance of the support, or metals such as aluminum may be added.

[0039] <Embodiment 1 Configuration: Catalyst dispersion shell (0102): Type of catalyst metal>: Mainly corresponds to claim 2 The catalytic metal dispersed in the shell is one or more metals selected from copper, nickel, iron, and ruthenium, or an alloy or intermetallic compound containing one or more metals selected from copper, nickel, iron, and ruthenium, and is configured so that the catalytic metals of the catalyst-dispersed porous core and the catalyst-dispersed shell are the same metal.

[0040] As the catalytic metal, transition metals that have highly reactive d-electrons and can take various oxidation numbers are suitable. Among transition metals, Cu, Fe, Ni, Ru, etc. are suitable as catalytic metals for methanol reforming because they have a high methanol conversion rate, produce little CO, which is not a desired reaction product, are highly resistant to the temperature and environment during the reaction, and are relatively inexpensive and easily available. Therefore, any one or more metals selected from Cu, Fe, Ni, and Ru, or an alloy or intermetallic compound containing one or more metals selected from Cu, Fe, Ni, and Ru are preferred. Other transition metals include Co, Pt, Rh, Pd, Ir, Mo, W, La, Ce, etc., and transition metal alloys such as CuNi and CuCo can be used. In addition, Cu-Zn-Al, Cu-Zn-Cr, Cu-Ni-Zn, Rh-Mn, Pd-Zn, Cu-ZrO, etc. can be used as intermetallic compounds. 2 system, Ni-Cl system, ZrO 2 can be used as a catalyst.

[0041] <Embodiment 1: Composition: Catalyst dispersion shell (0102): Weight percent range of catalyst metal>: Mainly corresponds to claim 4 In order to determine the weight percent of the catalytic metal to be dispersed in the shell, a core (silica gel manufactured by Fuji Silysia Corporation (CARiACT (registered trademark) G-10: average particle size 1.7 mm)) without any catalytic metal dispersed therein was coated three times with a silicon alcoholate sol solution containing copper acetate (not limited to copper acetate, the same applies below) which is a water-soluble catalytic metal salt prepared by the manufacturing method described below. Samples in which the core was coated three times as described above were prepared by changing the weight percent of Cu in the sol solution. The amount of Cu, which is the catalytic metal dispersed in the completed shell, was 45, 50, and 55 wt% relative to the total weight of the shell. Using such catalyst samples in which the catalytic metal Cu exists only in the shell, an experiment was conducted to measure the methanol conversion rate (%) per 1 g of sample with each specification (weight percent of Cu).

[0042] The experimental results are shown in Figure 4. In Figure 4, the horizontal axis shows the weight percent of Cu in the shell, and the vertical axis shows the methanol conversion rate (%), and an approximation line for the measurement results is also shown. The components other than Cu in the shell are SiO 2The results were as follows: the weight % of Cu relative to the shell was 45wt%, the methanol conversion was 80.4%, 50wt% was 93.0%, and 55wt% was 86.0%. The weight % of Cu that results in a methanol conversion of 50% or more is about 40.5% to about 61.5%. In this experiment, the catalyst-dispersed shell was coated three times, but if the number of coating times is reduced in consideration of the manufacturing process load, it is preferable to reduce the number of coating times with a specification of Cu weight % that has a high methanol conversion rate of the shell. Therefore, the lower limit of Cu weight % is preferably 45wt% or more so that the methanol conversion rate is 80% or more. The upper limit of Cu weight % that results in a methanol conversion rate of 80% or more is 55wt% or more according to the approximation line shown in FIG. 4. However, the inventor of the present invention found during the experiment that if the Cu of the shell exceeds 55wt%, sintering is likely to occur at the temperature during the methanol reforming reaction. Since sintering causes a decrease in the methanol conversion rate, the upper limit of the Cu weight percentage of the shell is preferably 55 wt% or less. Therefore, the preferred Cu weight percentage of the shell, which provides a methanol conversion rate of 80% or more, is 45 wt% to 55 wt%. The more preferred Cu weight percentage range of the shell is 48.1 to 53.9 wt%, which provides a methanol conversion rate of 90% or more.

[0043] <Embodiment 1 Configuration: Catalyst dispersion shell (0102): Manufacturing process load> The manufacturing method of the present invention will be described using examples after the description of the configuration.

[0044] <Dispersion of catalytic metals in the core> Dispersion of the catalytic metal in the core is performed by immersing porous granular silica gel or the like in a metal salt aqueous solution and permeating the aqueous solution into the pores of the silica gel or the like, as described in the manufacturing method of the catalyst of the present invention described later. The metal salt can be dispersed in the pores by using a metal salt aqueous solution with low viscosity. The amount of dispersion of the metal salt is adjusted by adjusting the concentration of the catalytic metal salt dissolved in the aqueous solution. After permeation, drying is performed in an environment of, for example, 120°C for 12 hours. Finally, the catalytic metal salt is heated at a high temperature, such as 400°C, at which the catalytic metal salt decomposes, and substances other than the catalytic metal in the catalytic metal salt are separated and removed as gas. For this reason, the catalytic metal is dispersed in the core only once. This is because repeated high-temperature heating is likely to cause sintering, in which the catalytic metal aggregates, and if the catalyst is re-immersed after drying, the catalytic metal salt that has been dried will dissolve in the permeated catalytic metal salt aqueous solution, making it difficult to achieve the desired dispersion amount.

[0045] <Shell Coating> For example, a sol solution is prepared by adding a silicon alcoholate such as tetraethoxysilane to an aqueous solution of a catalytic metal salt, and the sol solution is added to, for example, porous granular silica gel, stirred, and coated onto the surface of the silica gel. After coating, the coated sol solution is dried (e.g., at 120°C for 12 hours). After coating and drying a predetermined number of times, the solution is heated at a high temperature (e.g., at 400°C for 3 hours) to separate and remove substances other than the catalytic metal in the catalytic metal salt as gas, and the silicon alcoholate is calcined to produce SiO 2The sol solution is then oxidized to form a shell. During coating, the viscosity of the sol solution is high, so even if porous granular silica gel is used as the base for coating, it is difficult for the sol solution to penetrate into the pores. In addition, if the coated sol solution is dried and turned into a gel, it can be coated again by placing it on top of the original sol solution. The weight percentage of the catalytic metal salt contained in the coated and gelled original sol solution is constant for each and every coating, such as the first coating, the second coating, the third coating, etc., so the weight percentage of the catalytic metal in the finally formed shell is constant regardless of the number of coatings (the total amount of catalytic metal (g) contained in the shell naturally changes depending on the number of coatings). Since the shell needs to be dried after each coating, increasing the number of coatings increases the number of drying processes, lengthening the manufacturing period, and increasing the process load compared to dispersing the catalytic metal in the core.

[0046] <Embodiment 1 Configuration: Catalyst dispersion shell (0102): Number of coatings> Examination of the weight percentage of Cu dispersed in the catalyst dispersion shell During the prototype, coating was performed three times, but considering the load of the manufacturing process, it is better to have fewer coating times. Therefore, an experiment was conducted to examine the relationship between the number of coating times and the methanol conversion rate. The experimental sample used was a core with no Cu dispersed therein, and a silicon alcoholate sol solution containing, for example, copper acetate (not limited to copper acetate, the same applies below) was coated on the core a number of times so that the Cu content of the shell was 50 wt% when completed (the specification in which the methanol conversion rate was almost maximum when the shell Cu weight percentage was divided). The methanol conversion rate was measured using the prepared sample. The results of the investigation into the relationship between the number of coating times and the methanol conversion rate are shown in Figure 5. Figure 5 shows that the methanol conversion rate increases with the number of coating times. The samples with a methanol conversion rate of over 50% were coated twice or more, and the samples with a methanol conversion rate of over 80% were coated three times. As mentioned above, even if the number of coatings is increased, the weight percentage of the catalytic metal contained in the shell remains constant and does not increase. Therefore, even if the number of coatings is increased using a material in which the weight percentage of the catalytic metal contained in the shell formed by a single coating is 55 wt% or less, at which point sintering does not occur, the catalytic metal contained in the shell will not sinter.

[0047] However, as mentioned above, increasing the number of coating times increases the burden on the manufacturing process, so there is a demand to keep the number of coating times as low as possible. A single Cu dispersion on the core or a single shell coating does not reach a methanol conversion rate of 80%. Since a double coating still does not reach a methanol conversion rate of 80%, we next considered a core-shell structure with a single Cu dispersion on the core and a single shell coating, which is close to the double coating (no core support) in terms of the burden on the manufacturing process.

[0048] <Embodiment 1 Configuration: Core-shell configuration>: Mainly corresponds to claim 4 Next, we will explain the specifications for dispersing and supporting Cu in both the core and shell. Figure 6 shows the methanol conversion rate (black circles and a graph with a solid approximate line) of a catalyst prepared by coating the shell once on a core in which different weight percentages of Cu were dispersed (as before, all Cu in the shell was 50 wt%). The data for when the weight percentage of Cu dispersed in the core was 0 wt% was taken from the data for a sample in which the shell was coated a different number of times (Figure 5). The horizontal axis of Figure 6 shows the weight percentage of Cu dispersed in the core, and the vertical axis shows the methanol conversion rate (%) (approximation lines are also shown). The methanol conversion rate was 88.6% when 20 wt% of Cu was dispersed in the core.

[0049] Furthermore, based on the data on the methanol conversion rate of the catalyst prepared by coating the shell once on the cores dispersed with different Cu weight percentages in Figure 6 (all shell Cu was 50wt%, as mentioned above), and the data in Figures 2, 4, and 5, we estimated and plotted the methanol conversion rate of the catalyst prepared by coating the shell once on the cores dispersed with different Cu weight percentages when the shell Cu weight percentages were 45wt% and 55wt%. The graph for the shell Cu weight percentage of 45wt% is shown in Figure 6 with white circles and a dotted approximation line, and the graph for 55wt% is shown with white triangles and a dotted approximation line.

[0050] As shown in FIG. 6, the lower limit of the weight percent of Cu dispersed in the core is 5 wt% or more because there are few catalytic active sites when it is less than 5 wt%, and the methanol conversion rate of the catalyst with a core-shell structure at that time is 40% or more. Similarly, the upper limit at which the methanol conversion rate is 40% is 25 wt% (methanol conversion rate of 80% or more) at which sintering of Cu dispersed in the core does not occur. Therefore, as a catalyst, the weight percent of Cu dispersed in the core when the shell is coated once (weight percent of Cu dispersed in the shell is 45 to 55 wt%) is in the range of 5 to 25 wt%, and preferably 10 to 25 wt% at which the methanol conversion rate is about 60% or more. More preferably, the condition for a methanol conversion rate of 80% or more (obtaining the range from the approximation line in FIG. 6) is a range of 15 wt% to 25 wt% of Cu dispersed in the core and 47 wt% to 53.8 wt% of Cu dispersed in the shell when coated once.

[0051] From the results in Figure 6, the methanol conversion rate is higher for the sample with 10 wt% Cu core than for the sample with 0 wt% Cu core, even with the same one-time shell coating. Similarly, the methanol conversion rate is higher for the sample with 20 wt% Cu core than for the sample with 10 wt% Cu core. This shows that not only the shell's catalytic metal Cu but also the Cu dispersed in the core contributes to the methanol reforming reaction. At the beginning of the explanation of the catalyst-dispersed shell, we mentioned that the shell is porous based on the porosity evaluation (pore distribution evaluation) results of the shell material alone (Figure 3). From the results of the methanol conversion rate shown in Figure 6, we can see that the shell formed by the sol-gel method based on silicon alcoholate and water-soluble catalytic metal salt does not have a dense structure and completely covers the core, but has a porous structure or gaps that allow methanol vapor and water vapor to pass through.

[0052] <Embodiment 1: Structure: Core-shell structure: Measured by Cu weight per 1 g of catalyst> Figure 7 is a diagram that combines Figures 2, 4, and 6 used in the explanation so far, with the horizontal axis representing the Cu weight (g) per 1 g of catalyst of each specification composed of catalytic metal and carrier material, and the vertical axis representing the methanol conversion rate (%). The graph of white circles and dotted lines in Figure 7 shows the methanol conversion rate when there is no shell (represented as core support only) and the weight percentage of Cu is dispersed in the core (corresponding to Figure 2). The graph of white circles and solid lines in Figure 7 shows the methanol conversion rate when Cu is not dispersed in the core (represented as no core support) and the number of times the shell is coated is changed from 1 to 3 (corresponding to Figure 4). The graph of black circles and solid lines in Figure 7 shows the methanol conversion rate when the shell is coated once and the weight percentage of Cu dispersed in the core is changed (corresponding to Figure 6). Explanations of each graph are omitted because they were explained when Figures 2, 3, and 5 were first introduced.

[0053] In Figure 7, the methanol conversion rate of the sample coated twice with the shell is higher than that of the sample coated once with the shell and with 10wt% or 20wt% Cu dispersed in the core. These samples are a catalyst prepared in two steps, with the shell coated twice, and a catalyst prepared in two steps, with the shell coated once after Cu is dispersed in the core. From the graphs in Figure 7, the sample coated three times with the shell has the highest methanol conversion rate, but the process of forming the shell with Cu dispersed must be repeated three times, and the manufacturing process load is large with three steps. Therefore, the specification in which Cu is also dispersed in the core and the shell is formed by one coating, which is two steps, provides the best balance between the manufacturing load and the catalyst performance indicated by the methanol conversion rate. In the manufacturing method examined this time, the specification in which Cu is dispersed once with 20wt% in the core and the shell is coated once (Cu 50wt%) has the best methanol conversion rate of 88.6%. If an increase in the production load is tolerable, the number of coating steps may be increased to two or three to increase the total number of steps in order to further improve the methanol conversion rate.

[0054] <Embodiment 1: Structure: Core-shell structure: Advantages of the core-shell structure> The methanol-reforming hydrogen production catalyst of the present invention is characterized in that the catalyst-dispersed porous shell has a larger weight percent of the catalyst metal than the catalyst-dispersed porous core, as explained above. Another characteristic is that the pore diameter of the catalyst-dispersed porous shell has a pore distribution of 1.5 nm or less, with the first peak at 0.66 nm, the second peak at 0.972 nm, and the third peak at 1.49 nm (FIG. 3) (1.5 nm: the larger diameter foot of the third peak, the lower limit of the pore distribution is 0.63 nm, which is the smaller diameter foot of the first peak). The average pore diameter of the silica gel (G-10) used in this embodiment as the catalyst-dispersed porous core is 10 nm (according to the manufacturer's website), which is one order of magnitude larger than the pores of the shell. The diameter of a methanol molecule is about 0.4 nm. It is considered that the pores of the core of 10 nm are easier for the methanol molecule to proceed to the vicinity of the center than the pores of the shell. Therefore, the average pore diameter of the porous material used for the core is preferably 6 nm or more, which is 10 times the diameter of the methanol molecule, and is preferably about 14 nm or less, because if the pore diameter is too large, the particle diameter of the catalytic metal becomes large to maintain the weight percentage of the catalytic metal, and the efficiency as a catalyst decreases. On the other hand, experimental results show that the methanol conversion rate peaks at just under 80% when the amount of Cu supported on the core is 20 wt%, and even if the amount of Cu is increased beyond that, the methanol conversion rate decreases due to the effects of sintering. Therefore, when Cu is dispersed in the pores of the support later, there is a limit to the amount of Cu (wt%) that can be dispersed and the methanol conversion rate obtained.

[0055] On the other hand, a catalyst in which a shell was coated on a core that did not support Cu and the shell contained 50 wt% Cu achieved a methanol conversion rate of 93% with three coatings as mentioned above. The amount of Cu per 1 g of catalyst was 0.21 g, and the shell thickness estimated from the weight ratio of the shell to the core (0.71) was about 0.1 mm (core diameter about 1.7 mm). This method requires three coatings and three processes, which places a heavy burden on the manufacturing process. For comparison, when a granular catalyst of the prior art manufactured by the sol-gel method using the material forming the shell was examined, most of the reaction took place in the surface layer about 0.1 mm thick, and little reaction occurred in the center, so it is thought that the catalytic metal in the center was not used. With a specification of 50 wt% Cu, 0.5 g of Cu is contained per 1 g of catalyst. The weight of the Cu in the 0.1 mm thick surface layer is approximately 0.13 g, and the Cu contained in the 1.7 mm diameter sphere below the surface weighs approximately 0.37 g, which means that the approximately 0.37 g of Cu contained in this core is not being used effectively.

[0056] As explained above, in a configuration in which only a porous core is used and Cu is later dispersed in the pores of the core, it is not possible to support a large amount of Cu, and it is difficult to obtain a high methanol conversion efficiency. A high methanol conversion rate can be obtained by coating the shell three times, but the manufacturing process is burdensome. If the material that constitutes the core is manufactured so that it contains Cu (for example, by the sol-gel method) (conventional technology), a high methanol conversion rate can be expected, but the Cu below the surface layer of 0.1 mm thickness is not effectively utilized, and the utilization rate of Cu is low. These problems arise when Cu is dispersed only in the core or only in the shell, or when the same amount of Cu is uniformly dispersed in a porous granular catalyst.

[0057] Therefore, in the present invention, a core-shell structure is used in which Cu is dispersed and supported on the core, and a shell containing more Cu than the core is formed on the surface of the core, thereby making it possible to obtain a catalyst that achieves a high methanol conversion rate and has an improved Cu utilization rate compared to the conventional technology without significantly increasing the burden on the manufacturing process.For example, a catalyst with a core-shell structure in which the core is coated with 20 wt% Cu and the shell is coated with 50 wt% Cu once has a methanol conversion rate of 88.6% and a specification of 0.29 g of Cu in the catalyst, which saves more than 40% of Cu compared to the 0.5 g of Cu used in the granular catalyst in which Cu is uniformly distributed from the surface to the center of the conventional technology described above.

[0058] <Embodiment 1 Average particle size of catalyst>: Mainly corresponds to claim 5 The average particle size of the methanol-reforming hydrogen production catalyst of the present invention is preferably 1 to 5 mm. The smaller the average particle size of the produced catalyst, the greater the total surface area of ​​the catalyst placed in the reaction vessel, and therefore the higher the reaction efficiency. However, if the diameter is 1 mm or less, the gap between the catalyst particles becomes narrow, making it difficult for the raw material methanol vapor and water vapor to advance into the reaction vessel, and the pressure difference ΔP between the inlet and outlet of the reaction vessel increases (the pressure is higher at the outlet), resulting in a lower methanol conversion rate. If the bead diameter is 5 mm or more, the total catalyst surface area in the reaction vessel becomes small, resulting in a lower methanol conversion rate. For this reason, the above range is preferable.

[0059] <Embodiment 1 Manufacturing method>: Mainly corresponds to claim 6 First, the method for producing a catalyst having a core-shell structure according to the present invention will be described below with reference to Figures 8 and 9. The following embodiment will be described based on experiments conducted to verify the present invention, but the amounts of chemicals and raw materials used, heating time, etc. can be adjusted according to the amount of catalyst to be produced while maintaining the composition ratio.

[0060] <Embodiment 1 Manufacturing Method: Core: Core Preparation Step (S0901)> The core preparation step is a step of preparing a porous granular core of a desired diameter. In this embodiment 1, silica gel is used as the porous granular core. In the experiment, silica gel (CARiACT (registered trademark) G-10: average particle size 1.7 mm) manufactured by Fuji Silysia Ltd. was used. The average particle size of the core used is preferably about 1 to 5 mm. The shell that is coated on the core in a later step contains 45 to 55 wt % of catalytic metal and therefore has a thickness of about 0.1 mm. Therefore, the above-mentioned range is also preferable for the core.

[0061] If the core preparation step provides cores that are sufficiently clean for the purpose of producing a catalyst, then the subsequent pretreatment steps described below, such as removing impurities, may not be necessary. If there are concerns about cleanliness, impurities can be removed by carrying out a pretreatment step in which the impurities are removed by washing with an appropriate solvent such as water or acid, or by heat treatment.

[0062] The core preparation step includes purchasing manufactured cores that are generally available on the market, separating an amount of cores appropriate for the amount of catalyst to be manufactured, and setting the separated cores in a designated location in the device or equipment used for catalyst manufacturing. If the catalyst manufacturer manufactures the cores themselves, a core manufacturing step of manufacturing porous cores may also be included. If the catalyst manufacturer manufactures porous silica gel as the cores themselves, an appropriate manufacturing method can be selected, such as the sol-gel method, which generates silicic acid monomers by hydrolysis of silicon alcoholate (e.g., tetraethoxysilane), the phase separation method, or the sodium hydroxide method.

[0063] <Embodiment 1 Manufacturing method: Core: Core preparation step (S0901): Material> In this specification, silicon oxide (silica, SiO ) is used as the catalyst-dispersed porous core. 2 ) is described as an example, but the catalyst-dispersed porous core may be made of one or more of silicon oxide, aluminum oxide, zeolite, carbon, and metal oxide.

[0064] The core material is required to have four characteristics as described above, such as high support capacity, thermal stability, chemical stability, and interaction with the supported catalytic metal, as a substance that supports the catalytic metal used in the gas reaction. The support material that satisfies these characteristics is made of one or more of the above-mentioned silicon oxide, aluminum oxide, zeolite, carbon, and metal oxide.

[0065] <Embodiment 1 Manufacturing Method: Core: Pretreatment Step (S0902)> The pretreatment step is a step of washing the prepared porous core to remove impurities, so if a core that is sufficiently clean for the purpose of producing a catalyst can be obtained in the core preparation step, the pretreatment step of removing impurities may not be performed.

[0066] Possible pretreatment methods include washing by immersing in clean water (distilled water, more preferably pure water), heating at high temperature in an oxygen-containing atmosphere (air is also acceptable), etc. In this embodiment, heating is performed in air at 500°C for 2 hours (this also serves to calcine the silica gel used as the core in this embodiment).

[0067] <Embodiment 1 Manufacturing Method: Core: Core Dipping Step (S0903)> The core immersion step is a step of immersing the pretreated porous core in a solution in which a water-soluble catalytic metal salt is dissolved. When the porous core is immersed in the solution in which a catalytic metal salt is dissolved, the solution penetrates to the center of the porous core. The extent to which the solution penetrates into the porous core can be adjusted by adjusting the immersion conditions such as the immersion time. In consideration of the methanol conversion rate, it is preferable to penetrate to the center.

[0068] When the catalytic metal is Cu, for example, a copper nitrate solution is used. The concentration of the copper nitrate solution can be appropriately set according to the amount of Cu dispersed in the core. In addition to copper nitrate, water-soluble catalytic metal salts such as inorganic salts containing Cu (such as copper sulfate) and organic acid salts containing Cu, such as copper acetate, can be used. Examples include copper chloride, copper sulfate, copper carbonate, copper acetate, and copper ethoxide. Instead of immersing the core in the solution, the solution may be sprayed onto the core or poured into a container containing the core.

[0069] As the catalytic metal other than Cu, for example, one or more of nickel, iron, and ruthenium, alloys, or intermetallic compounds can be used. However, the metal is selected so as to be the same as the catalytic metal of the shell described below. Although the solution is described as an example using water as the solvent, an organic solvent such as ethanol may be used, or a mixture of water and an organic solvent may be used as long as the organic solvent is miscible with water.

[0070] As described above, transition metals that have highly reactive d-electrons and can take various oxidation numbers are suitable as catalytic metals. Among transition metals, Cu, Fe, Ni, Ru, etc. are suitable as catalytic metals for methanol reforming because they have a high methanol conversion rate, produce little CO, which is not a desired reaction product, are highly resistant to the temperature and environment during the reaction, and are relatively inexpensive and easily available. Therefore, any one or more metals selected from Cu, Fe, Ni, and Ru, or an alloy or intermetallic compound containing one or more metals selected from Cu, Fe, Ni, and Ru are preferred. Other transition metals include Co, Pt, Rh, Pd, Ir, Mo, W, La, Ce, etc., and transition metal alloys include CuNi and CuCo. In addition, Cu-Zn-Al, Cu-Zn-Cr, Cu-Ni-Zn, Rh-Mn, Pd-Zn, Cu-ZrO, etc. can be used as intermetallic compounds. 2 system, Ni-Cl system, ZrO 2 can be used as a catalyst.

[0071] When a porous core is immersed in a solution in which a catalytic metal salt is dissolved, the solvent of the solution remains in the pores of the core. In order to remove the remaining solvent, a drying step may be performed to dry the porous core in which the solution has penetrated. The drying is performed, for example, in an air atmosphere using a ventilated thermostatic chamber at 120°C for 12 hours.

[0072] In this embodiment, a copper nitrate aqueous solution in which copper nitrate, which is a salt of the catalytic metal Cu, is dissolved, is used as the solution to be immersed in the core. When the catalytic metal salt dissolved in a solvent is adsorbed on the porous support, the commonly used incipient wetness method is used. This method involves gradually adding a solution in which the catalytic metal salt is dissolved to the porous core until the amount is slightly more than the amount that can be adsorbed in the pores of the support (not too much, 1.5 times or less). In the experiment that obtained the data of this embodiment (FIGS. 2, 6, and 7) described above, the core immersion process was performed as follows. Note that a method other than the incipient wetness method may be used as a method for immersing (impregnating) the core with the solution.

[0073] <Embodiment 1 Manufacturing method: Core: Core immersion process: Solution preparation> When silica gel G-10 manufactured by Fuji Silysia Chemical Co., Ltd. is used as the core carrier as described above, the pore volume disclosed by the manufacturer is 1.3 ml / g. The amount of solution used for immersion is determined by this pore volume, and the copper nitrate concentration dissolved in the solution is adjusted. In this embodiment, 14 ml of copper nitrate aqueous solution was prepared by dissolving 3.8 g of copper (II) nitrate trihydrate in 14 ml of water for 9 g of silica gel G-10. The pore volume of 9 g of silica gel G-10 is 11.7 ml (based on data posted on the manufacturer's website: pore volume 1.3 ml / g), so it is set to 14 ml with some margin of error (+20%).

[0074] <Embodiment 1 Manufacturing method: Core: Core immersion process: Impregnation> The aqueous solution prepared above was impregnated (soaked) into 9 g of silica gel G-10. The aqueous solution was poured into a container containing silica gel, but depending on the impregnation method, the silica gel may be placed in a container containing the aqueous solution.

[0075] When impregnating (soaking) a porous core with an aqueous solution of copper nitrate or the like, simply immersing the core in the solution will result in the solution penetrating into the pores due to capillary action, but more effective penetration can be achieved by using methods such as vacuum penetration (adding an aqueous solution of copper nitrate or the like in a vacuum, and then gradually returning the pressure to atmospheric pressure), promoting penetration through vibration (ultrasonic vibration, etc.), or temperature adjustment (raising the temperature to reduce the viscosity of the liquid to be penetrated).

[0076] <Embodiment 1 Manufacturing method: Core: Core immersion process: Drying> The water, which was the solvent, was removed from the silica gel G-10 that had been impregnated (soaked) with the aqueous solution. The water was evaporated and removed by heating at 120° C. in an air atmosphere for 12 hours, and the copper nitrate was dispersed and arranged in the pores of the silica gel G-10.

[0077] <Embodiment 1 Manufacturing Method: Core: Core Catalyst Metal Supporting Step (S0904)> The core catalyst metal supporting process is a process in which the catalyst metal salt dispersed in the porous core is thermally decomposed to support the catalyst metal on the porous core. In order to thermally decompose the catalyst metal salt dispersed in the core, the core is heated at a high temperature, components other than the catalyst metal are removed from the catalyst metal salt solution immersed in the core, and the catalyst metal or oxidized catalyst metal particles are formed and supported on the core. One example of the conditions is heating at 400°C in an air atmosphere. For example, when copper nitrate is used as the solution in the core immersion process, the nitric acid component reacts with oxygen by heating at 400°C for 3 hours, and is discharged as nitrogen oxides and can be removed.

[0078] If the catalytic metal dispersed in the pores of the core is oxidized, it is better to reduce it before using it for methanol reforming, but the reduction process may be performed all at once with the catalytic metal of the shell after the shell is formed. Since a heat treatment in air is performed during the shell formation, even if the core alone is reduced, there is a possibility that it will be oxidized again during the shell-related process, so it is preferable to reduce it all at once, which eliminates one process.

[0079] <Embodiment 1 Manufacturing Method: Shell: Precursor Film Forming Step (S0905)> The precursor film forming step is a step of immersing the porous core that has been subjected to the core catalyst metal supporting step in a hydrolysis sol solution of silicon alcoholate in which a water-soluble catalyst metal salt is dissolved, to form a precursor film on the surface of the porous core. The precursor film is a pre-stage film that will form a silica film supporting the catalyst metal by heating in the shell forming step described later.

[0080] An example of the hydrolysis sol solution is a sol prepared by adding a water-soluble catalytic metal salt to a mixture of silicon alkoxide such as tetramethoxysilane or tetraethoxysilane and water, and stirring the mixture. As the water-soluble catalytic metal salt, a Cu salt that dissolves in water or an organic copper compound that undergoes a hydrolysis reaction can be used. Specific examples include copper chloride, copper sulfate, copper nitrate, copper carbonate, copper acetate, copper ethoxide, etc. Fine copper particles may be mixed in place of the water-soluble catalytic metal salt.

[0081] In the explanation of the manufacturing method, Cu is used as an example of the catalytic metal. Generally, transition metals that have highly reactive d-electrons and can take various oxidation numbers are suitable as catalytic metals. Among transition metals, Cu, Fe, Ni, Ru, etc. are suitable as catalytic metals for methanol reforming because they have a high methanol conversion rate, produce little CO, which is not a desired reaction product, are highly resistant to the temperature and environment during the reaction, and are relatively inexpensive and easily available. Therefore, any one or more metals selected from Cu, Fe, Ni, and Ru, or an alloy or intermetallic compound containing one or more metals selected from Cu, Fe, Ni, and Ru are preferable. Other transition metals include Co, Pt, Rh, Pd, Ir, Mo, W, La, Ce, etc., and transition metal alloys include CuNi and CuCo. In addition, Cu-Zn-Al, Cu-Zn-Cr, Cu-Ni-Zn, Rh-Mn, Pd-Zn, Cu-ZrO, etc. can be used as intermetallic compounds. 2 system, Ni-Cl system, ZrO 2 can be used as a catalyst.

[0082] <Embodiment 1: Manufacturing method: Shell: Precursor film formation process: Preparation of sol solution> In this embodiment, unless otherwise specified, the composition of the shell when completed is 50 wt% Cu / SiO 2 A sol solution prepared so that the composition of the shell was divided was used (the exception was an experiment in which the composition of the shell was divided). 7.85 g of copper (II) acetate monohydrate (Kanto Chemical Co., Ltd.) was added as a water-soluble catalytic metal salt to 120 ml of water (distilled water. Pure water is more preferable) and stirred at 40°C until dissolved. After the temperature of the dissolved copper acetate aqueous solution returned to room temperature, 8.67 g of tetraethoxysilane (Kanto Chemical Co., Ltd.) was added drop by drop to the copper acetate aqueous solution over about 2 hours. After the addition was completed, the mixture was stirred weakly for about 12 hours and then left at room temperature for one day. In this way, a sol solution was prepared.

[0083] <Embodiment 1 Manufacturing method: Shell: Precursor film formation process: Coating with sol solution> The porous core may be immersed in the prepared sol solution, or the sol solution may be coated or added to the core. When the sol solution is coated on the core, the cores may come close to each other and form lumps. Stir appropriately to separate the cores. After the sol solution is coated on the core, dry it in an air atmosphere at 120 degrees for 12 hours. Even during drying, it is recommended to stir appropriately so that the silica gel does not stick to each other and form lumps. The coated sol solution dries and becomes a gel.

[0084] <Embodiment 1 Manufacturing Method: Shell: Shell Formation Step (S0906)> The shell forming step is a step of thermally decomposing the water-soluble catalytic metal salt in the precursor film formed in the precursor film forming step to form a catalyst dispersion shell. In the shell forming step, for example, by heating at 400°C for 3 hours in an air atmosphere, the alcohol in the silicon alcoholate of the shell is evaporated, the water-soluble catalytic metal salt (copper acetate in this embodiment) is thermally decomposed to remove components other than the catalytic metal, and the catalytic metal or oxidized catalytic metal particles are supported on a shell made of silica having a three-dimensional network structure.

[0085] The silica of the shell produced in the shell-forming step is desirably porous, and may have a porous shape that reflects the porous shape of the core with which the silica is in contact.

[0086] By creating a catalyst with a core-shell structure in which the weight percentage of the catalytic metal (the same as the catalytic metal dispersed in the core) dispersed in the shell formed on the surface of the core is greater than the weight percentage of the catalytic metal dispersed in the porous core, a catalyst with a higher methanol conversion efficiency can be obtained than a catalyst using the same amount of catalytic metal.

[0087] <Overview of embodiment 2>: Mainly corresponds to claim 7 This production method is configured to include an activation step in which the catalytic metal contained in the methanol-reforming hydrogen production catalyst produced in embodiment 1 is reduced before the methanol reforming reaction is carried out. A production method in embodiment 2 based on the production method in embodiment 1 will be described with reference to Fig. 10. The steps from the core preparation step (S1001) to the shell formation step (S1006) shown in Fig. 10 are the same as those in embodiment 1, so their description will be omitted. Only the activation step (S1007), which is a step unique to the production method in embodiment 2, will be described.

[0088] <Embodiment 2 Manufacturing Method: Activation Step (S1007)> The activation step is a step of performing an activation treatment in a reducing atmosphere at a temperature range of 280°C to 320°C before use on the methanol reforming type hydrogen production catalyst prepared through the core preparation step to the shell formation step of the production method of the first embodiment. A gas serving as a reducing agent is supplied to create a reducing atmosphere. The gas can be, for example, hydrogen gas, CO gas, or a mixture of CO and CO. 2 A mixture of gases such as the above can be used.

[0089] The activation process for reducing the oxidized catalyst metal (copper oxide with at least the surface oxidized in this embodiment) dispersed in the shell and core of the catalyst to form the catalyst metal (Cu in this embodiment) is preferably performed not only once on the methanol-reforming hydrogen production catalyst immediately after it has been produced through the core preparation process to the shell formation process of the production method of embodiment 1, but also before methanol reforming is performed for each batch process, such as when methanol reforming is started and then interrupted.

[0090] The gas for reduction may be newly supplied, but hydrogen gas, CO gas, CO and CO generated by methanol reforming may be used. 2 A certain amount of any one or more of the mixed gases above can be stored and used as a reducing agent before the next methanol reforming. Since only substances generated in the methanol reforming reaction are used, they can be used without concerns about catalyst contamination.

[0091] After the reduction reaction in the activation process, methanol vapor and water vapor are introduced to carry out the methanol reforming reaction without replacing the atmosphere with air or other oxygen-containing atmosphere. When methanol reforming is interrupted (interruption with plans to resume), air is not introduced into the device, and the device is filled with an inert gas (nitrogen gas), which prevents an oxide film from forming on the surface of the catalytic metal (Cu, etc.) and a decrease in the efficiency of the reforming reaction.

[0092] <Effects> The core-shell structure of the methanol-reforming hydrogen production catalyst of the present invention has a core-shell structure in which the weight percentage of the catalytic metal (the same as the catalytic metal dispersed in the core) dispersed in the shell formed on the surface of the core is greater than the weight percentage of the catalytic metal dispersed in the porous core, thereby making it possible to obtain a catalyst with a higher methanol conversion efficiency (i.e., a catalyst with a higher utilization rate of the catalytic metal) than a catalyst using the same amount of catalytic metal.

Claims

1. A catalyst-dispersed porous core in which a catalyst metal is dispersed to a central portion; a catalyst-dispersed shell in which the catalyst metal is dispersed on the surface of the catalyst-dispersed porous core; and a structure in which methanol vapor and water vapor in the reaction vessel can permeate the catalyst-dispersed porous core and come into contact with the dispersed catalytic metal in the catalyst-dispersed shell.

2. 2. The methanol-reforming hydrogen production catalyst according to claim 1, wherein the catalytic metal is one or more metals selected from the group consisting of copper, nickel, iron and ruthenium, or an alloy or intermetallic compound containing one or more metals selected from the group consisting of copper, nickel, iron and ruthenium, and the catalytic metals of the catalyst-dispersed porous core and the catalyst-dispersed shell are the same metal.

3. 3. The methanol-reforming hydrogen production catalyst according to claim 1, wherein the catalyst-dispersed porous core is made of at least one of silicon oxide, aluminum oxide, zeolite, carbon, and metal oxide.

4. 3. The methanol-reforming hydrogen production catalyst according to claim 1, wherein the proportion of the catalytic metal in the catalyst-dispersed porous core is 5 to 25 wt %, and the proportion of the catalytic metal in the catalyst-dispersed shell is 45 to 55 wt %.

5. 3. The methanol-reforming hydrogen production catalyst according to claim 1, wherein the average particle size of the methanol-reforming hydrogen production catalyst is from 1 to 5 mm.

6. A core preparation step of preparing a porous granular core; A pretreatment step of cleaning the prepared porous core to remove impurities; a core immersion step of immersing the pretreated porous core in a solution containing a water-soluble catalytic metal salt; a core catalyst metal supporting step of thermally decomposing the catalyst metal salt dispersed in the porous core to support the catalyst metal on the porous core; a precursor film forming step of immersing the porous core that has been subjected to the core catalyst metal supporting step in a hydrolysis sol solution of silicon alcoholate in which a water-soluble catalyst metal salt is dissolved, to form a precursor film on the surface of the porous core; a shell forming step of thermally decomposing a water-soluble catalytic metal salt in the precursor film formed in the precursor film forming step to form a catalyst-dispersed shell; A method for producing a methanol-reforming hydrogen production catalyst comprising the steps of:

7. A method for producing a methanol-reforming hydrogen production catalyst, comprising the step of: subjecting the methanol-reforming hydrogen production catalyst according to claim 6 to an activation treatment in a reducing atmosphere at a temperature range of 280°C to 320°C before use.

8. 8. The method for producing a methanol-reforming hydrogen production catalyst according to claim 6, wherein the catalytic metal is one or more metals selected from the group consisting of copper, nickel, iron and ruthenium, or an alloy or intermetallic compound containing one or more metals selected from the group consisting of copper, nickel, iron and ruthenium, and the catalytic metals of the core and shell are the same metal.

Citation Information

Patent Citations

  • Methanol steam reforming catalyst, methanol steam reforming device, and hydrogen generation method

    JP6936338B2

Cited By

  • Catalyst for on-line methanol reforming hydrogen production and preparation method thereof

    CN121372406A